On some properties of the stable stochastic processes - Kalinauskaitė, N. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Н. Калинаускайте. Некоторые свойства устойчивых случайных процессовN. Kalinauskaitė. Kai kurios atsitiktinių stabilių procesų savybės